The Relationship between the Frequency of Technology Use and Electronic Commerce Adoption among Small and Medium-Sized Enterprises in Kuwait - Mohd Isa, Salmi; Alenezi, Saleh (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research paper Research aims: This study aims to investigate the determinants of SMEs’ e-commerce adoption as well as technological, organisational, and environmental characteristics in Kuwait. Moreover, it aims to study the effect of the frequency of technology use as a moderator in SMEs’ e-commerce adoption. Design/Methodology/Approach: A questionnaire-based survey was conducted among 259 SMEs. Research findings: The results demonstrate a positive relationship between relative advantage, competitive pressure, and e-commerce adoption. Analysis of the level of technology use as a moderator reveals a significant difference in terms of the impact of compatibility, complexity, and supplier or customer pressure on e-commerce adoption. Theoretical contribution/originality: This study may be the first to assess the moderating role of the frequency of technology use in the context of SMEs’ e-commerce adoption. Research limitation/implications: The paper contributes to e-commerce adoption research by highlighting the main influencing factors, identifying several important interactions based on the frequency of technology use, and recognising many practical implications for SME managers. Keywords: E-commerce adoption, Frequency of technology use, Kuwait, SMEs, TOE JEL Classification: M10, M15, M31